‘n Pneumatologiese benadering tot die teologie - Brand, S. J. P. (Verbum et ecclesia, 2007)
This article investigates the relationship between the subjective experiential side of faith and the objective rational side thereof. The two Theologians, Karl Rahner and John Calvin both propose, from different perspectives, a unity between rationality and experience. A Pneumatological approach emphasizes a theology of accountability and responsibility (teologie van verantwoording). This theology acknowledges the importance of man’ s experience and man’ s search for purpose and meaning. Furthermore, from a criptural point of view, God places man in various relational contexts. God expects responsibility/accountability towards Him, towards one’ s fellow man and the whole of creation. Man’ s response is initiated in prayer guided by the Holy Spirit. In fulfilment of his/her personal responsibility/accountability a sense of meaning and purpose is achieved.